An autopsy view of the Hemi‐commando procedure. Issue 2 (1st December 2020) - Chaud, German J.; Perron, Jean; Pagé, Sylvain; Laflamme, Maxime; Côté, Jean‐Marc; Jacques, Frédéric
Abstract: Invasive endocarditis involving the fibrous skeleton of the heart requires complex high‐risk surgical management. For combined aortic and mitral infection in whom the posterior mitral leaflet and at least the free edge of anterior mitral valve could be spared, a modification of the Commando procedure was suggested: the "Hemi‐commando procedure." We report the autopsy images of a Hemi‐commando procedure after in unfortunate death in a 24 years old man 17 days after surgery.